Residential support for energy efficiency by utility organizations in the Southeast US. (10th March 2018) - Craig, Christopher A.
Abstract: This study examined residential policy support for energy efficiency (EE) subsidies for investor-owned utility organizations in the southeast United States. Residents in this region continue to increase electricity consumption, and utility organizations remain reliant on fossil fuels for generation. States in the region are resistant to federal clean energy policy. Investor-owned utilities in the region have offered residential EE programs, however, with mixed results. The study explored the likelihood that awareness of EE, past participation in EE, perceptions about utility motives for offering EE, socio-economic factors, attitudes, and planned behaviors would influence residential policy support for EE subsidies for utility organizations. Drawing from the theory of planned behavior, the study is the first to the author's knowledge to explore the mediating role that residential attitudes and planned behaviors occupy between the focal intrinsic and socio-demographic variables in the study and residential policy support for EE. The study found that the influence of Democratic affiliation on residential EE policy support was fully mediated through both attitudes and planned behaviors, and that perceptions of utility motives were fully mediated through planned behaviors. A large gap between attitudes and planned behaviors emerged for Democratic affiliates. Partially mediated relationships emerged for awareness in EE programs, past participation in EE programs, gender, and perceptions of utility motives. Gain- and loss-framing of messages was introduced and was significantly related to both residential attitudes and planned behaviors. The use of effective messaging strategies and implications for policy makers, utility organizations, and energy efficiency implementers are discussed. Highlights: Utility efficiency efforts have shown mixed results in reducing energy in the US. To meet GHG reduction and demand goals by utilities, residential EE is needed. Residential support is needed to enact EE policy to provide utilities subsidies. Democrat EE policy support was fully mediated through attitudes, planned behaviors. Awareness, participation, gender, and perceptions partially mediated policy support.